Visualising numerals: An ERPs study with the attentional SNARC task. (April 2018) - Pinto, Mario; Fattorini, Enrico; Lasaponara, Stefano; D'Onofrio, Marianna; Fortunato, Gianfranco; Doricchi, Fabrizio
Abstract: Inspecting or transforming the position of Arabic numbers in mental space helps everyday mathematical calculations. Nonetheless the neural and functional bases of this ability are poorly understood. Here we show that imagining the position of Arabic numbers on a horizontal mental number line speeds up the detection of targets appearing at corresponding positions in visual space. No similar advantage is found when numbers are merely perceived or classified according to their magnitude. Imagery enhanced electrophysiological activity in the extrastriate cortex contralateral to the imagined number position. Speeded detection of targets that were spatially congruent with the imagined number position was matched with enhanced C1 responses in primary visual cortex. In contrast, imagery had no effect on later target-related responses that are usually modulated by spatial attention. These results shed new light on the mechanisms that evoke sensory-like spatial representations of Arabic numbers in everyday mental computations.